Influence of E-Service Quality on Customer Satisfaction & Word of Mouth in App-based Service Industry: A Case on Pathao, Bangladesh - Karim, Rashed (Journal of Technology Management and Business, 2020)
This study aims to recognize the influence of electronic service (e-service) quality on satisfaction and word of mouth. The existing literature was reviewed to discover the e-service dimensions that have a positive influence on customer satisfaction. Multiple studies also indicate a strong link between satisfaction & word of mouth. Surveys were conducted by distributing the structured questionnaires to gather data for this study. The sample size is 186 and is chosen on a convenient basis and indicators were generated based on prior literature review. Data has been analyzed by using PLS software. SPSS software package was also used to present the data demographically and to convert the data for SmartPLS (version 3). The result shows that there is a significant positive relationship between e-service quality dimensions and satisfaction followed by significant positive association with word of mouth as well. This study contributes to getting an insight into growing technology & its adaptability.